Interactions between the gut microbiota-derived functional factors and intestinal epithelial cells – implication in the microbiota-host mutualism - Kaur, Harpreet; Ali, Syed Azmal; Yan, Fang (Frontiers in Immunology, 2022)
Mutual interactions between the gut microbiota and the host play essential roles in maintaining human health and providing a nutrient-rich environment for the gut microbial community. Intestinal epithelial cells (IECs) provide the frontline responses to the gut microbiota in maintaining intestinal homeostasis. Emerging evidence points to commensal bacterium-derived components as functional factors for the action of commensal bacteria, including protecting intestinal integrity and mitigating susceptibility of intestinal inflammation. Furthermore, IECs have been found to communicate with the gut commensal bacteria to shape the composition and function of the microbial community. This review will discuss the current understanding of the beneficial effects of functional factors secreted by commensal bacteria on IECs, with focus on soluble proteins, metabolites, and surface layer components, and highlight the impact of IECs on the commensal microbial profile. This knowledge provides a proof-of-concept model for understanding of mechanisms underlying the microbiota-host mutualism.